Early Hepatic Complication in First Year after Bone Marrow Transplantation in Major Beta Thalassemic Patients - M Iravani; M Arshy; M Toutounchi; L Nedaeifard; A Ghavamzadeh (International Journal of Hematology-Oncology and Stem Cell Research, 2005)
Introduction: Bone marrow transplantation is a good therapeutic modality for beta thalassemia. Liver complications are one of the major causes of morbidity and mortality following BMT. Determination of the factors of liver injury leads to earlier  diagnosis after BMT and improves prognosis. Method: We studied 113 major Beta thalassemic patients who have been transplanted from 1990- 2000 in bone marrow transplantation center of Shariati Hospital. 62 were male and 51 were female. 27 pa¬tients were class one, 56 were class two and 30 were class three. The median age of each class were 6.5, 6.3 and 8.7. Conditioning regimen consisted of busulfan (3.5-4mg/Kg) and cyclophophamide (40-50mg/Kg).For GVHD prophylaxis we gave cyclosporine ± metothoroxate. Grade of liver fibrosis de¬fined by biopsy in all patients before BMT. All patients and their donors tested for HBSAg, HBSAb, HCVAb, CMVAb with RIA method. We assessed causes of liver dysfunction before and after trans¬plantation and effect of high ferritin level on liver function. Results: Hepatic dysfunction in first year after transplantation was seen in 86 (76%) patients. Causes of liver dysfunction were consisted of 53.1% GVHD, 15.93% cyclosporine hepatotoxicity, 7.07% condi¬tioning regimen hepatotoxicity and VOD. In all three classes hepatic GVHD, cyclosporine toxicity, death and normal liver function post BMT had significant relation with hepatic dysfunction before BMT (P=0.001). In patients with ferritin level more than 1000, there were significant hepatotoxicity with conditioning regimen (P=0.001). 17 (15.04%) of patients have been died. Discussion: According to our study hepatic GVHD (%53.1) is the most common cause of hepatic dys¬function in all three classes.